2020
DOI: 10.3389/fphar.2020.00406
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetic, Pharmacogenetic, and Pharmacodynamic Analysis of Cyclophosphamide in Ethiopian Breast Cancer Patients

Abstract: Cyclophosphamide (CPA) containing chemotherapy regimen is the standard of care for breast cancer treatment in sub-Saharan Africa. Wide inter-individual variations in pharmacokinetics (PK) of cyclophosphamide (CPA) influence the efficacy and toxicity of CPA containing chemotherapy. Data on the pharmacokinetics (PK) profile of CPA and its covariates among black African patients is lacking. We investigated population pharmacokinetic/pharmacogenetic/pharmacodynamic (PK-PG-PD) of CPA in Ethiopian breast cancer pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Our results agree with the findings of this study. BSA, which was an independent variable for predicting the AUC/Ds of DXR and CPA in this study, has been reported to affect pharmacokinetics parameters in other studies [22][23][24] . In addition, in this study, a negative correlation between Alb and AUC/D of DXR was found in elderly patients.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Our results agree with the findings of this study. BSA, which was an independent variable for predicting the AUC/Ds of DXR and CPA in this study, has been reported to affect pharmacokinetics parameters in other studies [22][23][24] . In addition, in this study, a negative correlation between Alb and AUC/D of DXR was found in elderly patients.…”
Section: Discussionmentioning
confidence: 56%
“…To the best of our knowledge, the effects of patient factors, such as sex, BSA, and biochemistry covariates, on VCR CL in elderly patients have not yet been clarified. Recently, it has been reported that gene polymorphisms of drug-metabolizing enzymes or transporters affect the pharmacokinetics of these cytotoxic anticancer drugs 23,[27][28][29][30] . Thus, various factors have a potential impact on the pharmacokinetic exposure of elderly patients receiving CHOP therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, two studies, one on tamoxifen and another on cyclophosphamide among breast cancer patients, have been performed in Ethiopia. 26 , 179 Another study was focused on AIs in South African women with breast cancer. 74 We would like to stress that Ethiopia has a complex admixture component with a dynamic history of several Eurasian ancestries and some Nilotic and Semitic-Cushitic components.…”
Section: Discussionmentioning
confidence: 99%
“…In Ethiopia, it has been reported that carriers of CYP3A5*3 and CYP3A5*6 had lower cyclophosphamide elimination rate and longer half-life than subjects carrying the wild-type allele. 179 Additionally, increased drug clearance has been reported in carriers of CYP2C9 *2 and CYP2C9 * 3 , 179 similar to the increased activity for other substrates. 180 Allele frequencies for these genes were previously reported in other sections.…”
Section: Cyclophosphamidementioning
confidence: 92%
See 1 more Smart Citation